Ailanthus grandis Prain-its Prospect in Forestry - Guhathakurta, P.; Ghosh, R. C. (Indian Forester, 1972)
Ailanthus grandis, Prain wlth several desirable characters in external form and behavior, namely, quicker rate of growth relative to others in association, a straight cylindrical bole without unwanted flares at the base and not too great a taper at the top, a restricted crown enabling a greater economy of the aerial space, habit of natural pruning, apical dominance of shoots and a thin back, has become eminently suitable for maximising production within a short span of time. The wood too can be put to several uses including box planking, match making and newsprint grade of pulp. From plantations raised since 1921 a relationship of the age wlth girth, height and volume of individual trees and some crop data bave been established. Some basic information too bas been gathered from current trials. Erratic in flowering and fruiting, Ailanthus has a long period of dormancy breaking with the onset of monsoon and a low viability; in a good seed year seed dibbling and in poor years, one-year old oursery stock outplanting in containers are the best methods of raising a successful plantatin. Naked root or ball of earth planting is not as efficient. Stumping has failed so far though it does not seem to be totally impossible. A taungya with a low vegetabie crop in the first year makes invaluable assistance io establlsbing young plantations. An early planting in favourable weather results in superior height growth. The greatest obstacle to extension of Ailanthus grandis in the duars is its aversion to excess moisture in the seedling stage. In these areas, the micro-relief produces zones of impeded drainage. To combat this, the ridge planting has been found to be successful. At present, large areas in the bhabar where draiilage poses no problem are beinagbrought under Ailanthus grandis with Bombax ceiba Linn. And it seems to be possible to harvest such a crop at 35-40 years and the final crop from principal species, Ailanthus alone will yield 20 m2 per hectare per annum. This plus out-turn from intermediate thinnings and final harvest of Bombax ceiba should go to qualify the crop as economically viable. In the duars where the species bad setbacks, Ailanthus is being mixed with Michelia champaca, Linn. And Bombax ceiba. Here the question of predominant role of Ailamhus Is uncertain, and unlike, in the bhabar where it Is possible to manage a crop of predetermined composition, tbe strategy of management at present is highly flexible.